Evaluation of phytoplankton phenology in the northern Bay of Bengal using ocean color remote sensing - Md Leion Hassan; Md Enamul Hoque; Md Nahin Alam; Md Ibrahim; Sheikh AftabUddin; Muhammed Forruq Rahman; Mamun Abdullah Al (Continental Shelf Research, 2026)

Toxic footprints: Unveiling phenolic micropollutants of Indian freshwater ecosystems - Soma Das Sarkar; Subir Kumar Nag; Md. Aftabuddin; Ajoy Saha; Sanjeev Kumar Sahu; Kavita Kumari; Sudarshan Bandyopadhyay; Basanta Kumar Das (Science of The Total Environment, 2025)

Assessment of three prokaryote primers for concurrent and comprehensive profiling of methanogen and methanotroph community and habitat specificity in three distinct wetland sediments - Kavita Kumari; Malay Naskar; Md. Aftabuddin; Uttam Kumar Sarkar; Subir Kumar Nag; Bandana Das Ghosh; Basanta Kumar Das (Journal of Soils and Sediments, 2025)

Intertidal macroinvertebrate community structure in a subtropical channel is driven by sediment properties across different land-use types - Mamun Abdullah Al; Aysha Akhtar; Hillol Barua; Abu Hena Mustafa Kamal; Md. Shafiqul Islam; Sheikh AftabUddin; Mohd Hanafi Idris; Muyassar H. Abualreesh; Letizia Modeo (Environmental Science and Pollution Research, 2022)

Status, Potential, Prospects, and Issues of Floodplain Wetland Fisheries in India: Synthesis and Review for Sustainable Management - Uttam Kumar Sarkar; P. Mishal; Simanku Borah; Gunjan Karnatak; Ganesh Chandra; Suman Kumari; D. K. Meena; Dipesh Debnath; Sona Yengkokpam; Pronob Das; Piyashi DebRoy; Anil K. Yadav; et al. (Reviews in Fisheries Science & Aquaculture, 2021)

Tropical hilsa shad ( Tenualosa ilisha ): Biology, fishery and management - M. Shahadat Hossain; S. M. Sharifuzzaman; Muhammad Abdur Rouf; Robert S. Pomeroy; Md Delwer Hossain; Sayedur R. Chowdhury; Sheikh AftabUddin (Fish and Fisheries, 2019)
Tropical hilsa shad, which is an anadromous fish migrating from the sea to spawn in freshwater river, constitutes an important fishery in some Asian and Middle East countries, particularly in Bangladesh. But, historical information on hilsa biology and ecology has confronted the scientists and policymakers with research and management challenges. We have reviewed both the old and recent findings on hilsa fishery to document the status of knowledge and potential gaps, necessary to comprehend for formulating a more effective fishery management plan. Thus, there has been a decline in hilsa catches in the riverine system associated with shift in fish migration routes, indiscriminate harvesting of brood and juvenile fish, and degradation of habitat. Specifically, the riverine hilsa catches peaked in the 1960s, declining thereafter, and became relatively abundant in marine waters since 1990s. Biological data indicated that hilsa goes through multiple reproductive cycles; therefore, a comprehensive understanding of reproductive biology, recruitment by various cohorts, stock abundance and habitats across the life cycle are necessary to accurately impose fishery regulatory measures, such as fishing ban in spawning season in Bangladesh. Moreover, domestication initiative is important for artificial seed production and mariculture development of hilsa that can not only offer economic return to small‐scale farmers but also reduce the growing pressure on capture fishery. Importantly, the arrangement of co‐management is found ideal as fishermen, scientists and managers can work jointly to improve the regulatory processes and to sustain the hilsa fishery over time.

IIKmTA: Inter and Intra Kingdom miRNA-Target Analyzer - Chittabrata Mal; Md. Aftabuddin; Sudip Kundu (Interdisciplinary Sciences: Computational Life Sciences, 2018)

Effective utilization of distiller’s grain soluble—an agro-industrial waste in the feed of cage-reared minor carp Labeo bata in a tropical reservoir, India - M. A. Hassan; Md. Aftabuddin; D. K. Meena; P. Mishal; S. Das Gupta (Environmental Science and Pollution Research, 2016)